A palynological investigation of vatica L. (dipterocarpaceae) in Peninsular Malaysia - El-Taguri, Houssein M.A.; Latiff A., (Universiti Kebangsaan Malaysia, 2014)
Pollen morphology of 24 species of Vatica L. had been investigated using light and scanning electron microscopes. Vatica is a stenopalynous genus, the pollens are radially symmetrical, isopolar, subprolate to suboblate sometimes prolate rarely oblate, all tricolpate. Exine ornamentation varies from thin to medium reticulate. On the basis of pollen shape two groups of Vatica have been recognized. Within the genus pollen diversity is valuable for identification and delimiting species.